Effects of Regular Follow-up on Quality of Life and Warfarin Efficiency in Rural Patients - Kılıç, Salih; Saraçoğlu, Erhan; Çekici, Yusuf; Kılıç, Dilara Deniz; Yıldırım, Arafat; Kuzu, Zülfiye (European Journal of Therapeutics, 2023)
Objective: This study aims to evaluate the effects of regular follow-up and education on warfarin efficiency, satisfaction, and the quality of life in patients from rural areas. Methods: A total of 133 patients from rural areas taking warfarin were followed up for the mean of 17.4±0.5 months (mean age 58±13 years, 72.9% female). All patients were educated and followed up by a single cardiologist prospectively. A list and an illustrated booklet presenting foods that interact with warfarin and a follow-up chart were prepared for each patient. An illustrated scheme of pills that were to be taken every day was prepared for illiterate patients. The international normalized ratio (INR) values during and 1 year before the study were recorded from the hospital system, and the time in therapeutic range (TTR) was calculated. The Duke Anticoagulation Satisfaction Scale was conducted at the start and end of the study to determine patients’ satisfaction with warfarin use. Furthermore, the Medical Outcomes Study Form 36 (SF-36) was used for determining the health-related quality of life (HRQoL). Results: A total of 45.9% of patients were illiterate, and 33.8% were primary school graduates. The median TTR during the follow-up increased significantly compared with the previous year [40.0 (IQR 36.5) vs. 62.1 (IQR 29.3); p<0.001]. Furthermore, the number of patients with TTR>70% increased significantly (36.8% vs. 21.1%, respectively; p<0.001). Unfortunately, patients’ HRQoLnand satisfaction with warfarin use were found to have deteriorated significantly compared to the basal levels. Conclusion: We found that the efficiency of warfarin increased significantly, but interestingly, HRQoL and the satisfaction with warfarin use deteriorated significantly after regular education and follow-up in patients from rural areas.